Webalyt: Implemetation of architecture for capturing web user behaviours with feedback propagation - Filip, Petr; Čegan, Lukáš (IEEE (Institute of Electrical and Electronics Engineers), 2018)
In the world of the Internet where people are consuming web-content, more and more emphasis is placed on user friendliness of web-pages. It means increasing web-page usability and better user-experience. Increasing quality of user-experience (UX) is the task of UX developers. They should always base their work on the best practices and research. Each webpage has its own specificity and it leads to new challenges for the UX developers. One of the biggest issues is the problematic view of a web-page on specific devices with specific web-browser versions. Tools for capturing user behaviour are available, but there are issues with data ownership and with the development of new functionality. Actually, there are no free easily scalable and extendable products for user data gathering on the market. In this paper, implementation of architecture (based on Spring Boot microservices) for capturing web user behaviours with feedback propagation is introduced. Architecture implementation is easily scalable and extendable. All of the components are described in detail. At the end of this paper, summary and limitation of created architecture is discussed. Webalyt is helpful for understanding user behaviour and improving user-experience.
Webalyt: implementace architektury pro získávání chování uživatelů webu s propagací zpětné vazby
Keywords: User-Experience; Web User Behaviour; Analytical Tool; Microservices; Spring Boot; Uživatelská přívětivost; Chování uživatelů; Analytický nástroj; Microservices; Spring Boot